An Updated Systematic Review and Meta-analysis of the Short- and Long-term Outcomes of Percutaneous Coronary Intervention for Patients with Severe Left Ventricular Systolic Dysfunction - Nuremanguli Abudukeremu§; Zi- Xiang Yu1§; Yi-Ning Yang; Siew- Pang Chan; Xiao-Mei Li; Fen Liu; Yi-Tong Ma (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
Background: Coronary artery disease (CAD) is the most common cause of left ventricular dysfunction (LVD). Confl icting evidence exists with regards to available treatments and patient prognosis. Revascularization may improve ventricular function while coronary artery bypass surgery (CABG) has signifi cantly improved survival. The effectiveness of percutaneous coronary intervention (PCI) has also not been thoroughly investigated to date. Objectives: To ascertain the in-hospital and long-term (≥1 year) outcomes of CAD patients with LV systolic dysfunction (ejection fraction ≤40%) after PCI according to a meta-analysis. Methods: A systematic literature search and a series of random-effect meta-analyses were conducted to evaluate the short- and long-term outcomes of PCI of the selected studies. Single-center studies andthose that did not report evidence on long-term mortality were excluded in the analysis. All statistical tests were performed with 95% confi dence intervals. A p-value of less than 0.05 was considered statistically significant.